Buy, borrow, die: how rich live off their paper wealth and avoid paying taxes and why we let them do it? - Smagurauskaitė, Agnė; Šarauskaitė, Gabrielė (Vilnius University Open Series, 2023)
In 2021, there are reportedly 2,755 billionaires on Earth, with an estimated total net worth of $13.1 trillion. Every year the newspaper Forbes conducts the list of World Billionaires, but we need to acknowledge that, not all billionaires and their wealth gets reported. Usually, the net worth is reported by calculating the number of stocks with the number of shares that the person owns. We take into consideration that the number we see in the newspaper exists only on paper, but the amount of money in the bank account of Billionaire does, not reflect that kind of wealth in any shape and form.Paper wealth differs from “real” or actual wealth, which is the value of the physical assets that are at the disposal of an individual or company. Many individuals and corporations fall victim to the paper wealth trap. On paper, it looks as though the assets logged are worth a certain amount, but the real assets in hand do not add up to the same. In order to assess, the real wealth individual has to realize the asset in the market by selling the asset mentioned below. If the taxpayer sells these assets, it has accumulated capital gains, then the taxpayer is subject to capital gains taxes.By using the tax planning strategy “Buy, Borrow, and Die” the wealthy individual avoids paying the capital gain tax on the assets that they have. This principle suggests buying and holding assets as they appreciate tax-free, as well borrow using the assets as leverage and using debt to reduce or eliminate income and estate taxes, and maximize aftertax wealth accumulation, as well after the taxpayer pass away the heirs, sell the whole wealth is tax-free, and the debt is paid with the tax-free proceeds.
Keywords: tax avoidance; taxation; investment; tax strategy